Hoax News Detection Using Passive Aggressive Classifier And TfidfVectorizer - Maulana Fajar Lazuardi; Renaldy Hiunarto; Kareena Futri Ramadhani; Noviandi Noviandi; Riya Widayanti; Muhamad Hadi Arfian (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2023)
Indonesia is one of the countries with the highest number of social media users. Million social media users in Indonesia reached 167 million in January 2023. These users are spread, across various social media, including Twitter with 24 million users. The high number of social media users on Twitter makes the information validation process even more neglected. Moreover, the trend of news interest read by social media users is only adjusted to their individual tastes. This phenomenon is evidenced by the large number of fake news (hoaxes) circulating in society which are spread through social media. Therefore, an accurate machine learning model is needed to classify